Mechanical influence of thread pitch on orthodontic mini-implant stability - Amanda Carneiro da CUNHA; Amanda Osório Ayres de FREITAS; Mariana MARQUEZAN; Lincoln Issamu NOJIMA (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The aim of this study was to evaluate the effect of pitch distance on the primary stability (PS) of orthodontic mini-implants (MIs) in artificial bone. Twenty experimental MIs were allocated to two groups, according to their geometric design: G1(30oX 0.6 mm) and G2(45o X 0.8 mm), and inserted into artificial bone of different densities: D1 (0.32 g/cm3) and D2 (0.64 g/cm3). The maximum insertion torque (IT) and removal torque (RT) values were recorded in N.cm. Loss of torque (LT) values were obtained by calculating the difference between the IT and RT. MI mobility was measured by means of a Periotest assessment. Normality and homogeneity were determined by means of the Kolmogorov-Smirnov and Shapiro-Wilk tests, respectively. A two-way ANOVA was used to detect differences between the mini-implant design and density factors. The ANOVA/Tukey tests were used to determine the intergroup difference. Higher IT values were observed for G2 (p ≤ 0.05) in D2. No statistical difference for RT was observed between the groups, whereas G2 presented higher values only for LT (p ≤ 0.05). The Periotest values (PTV) were higher for G1, in comparison with G2, in D1. G1 presented better PS in D2 (IT, RT and LT), whereas G2 was found to be more stable in D1, after evaluation with Periotest.